Desenvolvimento de metodologia para separação e identificação de impurezas provenientes de degradação forçada no fármaco carboplatina visando sua aplicabilidade na indústria farmacêutica - Honda, Tairine (Universidade Federal de São Carlos, 2025)
Cancer medications such as carboplatin are essential for improving patient survival rates and quality of life. Carboplatin, a platinum complex widely used in clinical practice, is susceptible to degradation processes that may generate impurities with potential impacts on drug safety and efficacy. Therefore, this study focused on applying high-resolution chromatographic and spectrometric techniques to elucidate degradation products formed under dry thermal stress conditions in the product Fauldcarbo, which contains the active ingredient carboplatin. We employed high-performance liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS) using electrospray ionization and a quadrupole time-of-flight (Q-TOF) analyzer, which enables high precision in mass determination and structural identification. We successfully identified the structure of both the known carboplatin impurity 1,1-cyclobutanedicarboxylic acid m/z 143,0345 (ESI-) and a previously unknown impurity m/z 404,0415 (ESI+). The unknown impurity was formed through the reaction of carboplatin with radical oxygen species, a process that may be favored by the high temperatures employed during stress conditions. This research not only enhanced our understanding of carboplatin degradation but also demonstrated the feasibility of analytical techniques for impurity monitoring, contributing to pharmaceutical quality and innovation.
Development of a methodology for separation and identification of impurities from forced degradation of the drug carboplatin focusing on its applicability in the pharmaceutical industry
Keywords: Carboplatina; Degradação forçada; Identificação de impurezas; Carboplatin; Forced degradation; Impurity identification; CIENCIAS EXATAS E DA TERRA::QUIMICA